(untitled) (Eurasian Journal of Philology Science and Education, 2016)
It is known that the special place in Turkic epic tradition is taken epos «Arzu-Gamber». This epos was many times built from lips of many peoples in many regions, was widespread in a hand-written form, was published as the book in Turkey, Iraq, Azerbaijan, the Southern Azerbaijan, in many countries of Europe. Purpose of this article research of numerous manuscripts epos «Arzu-Gamber». The author studies the manuscripts stored in libraries of Turkey, Austria, Holland, Turkmenistan This folklore text introduced as «bayatili dastan» (the epos with quatrains) among Azerbaijanians is presented as «hikaye» (tale), «masal» (story), «halk hikayesi» (folk tale) in other nations. It is interesting that being not very large this epos is still living nowadays among all Oghuz Turks such as – Azerbaijanians, Turkish, Gagauz, Turkmen, Turkmens from Kerkuk, Nogays, Crimea Tatars, even Urums and other Turk nations. More than forty variants of this epos have been collected from Turk nations by us. The geographical area of «Arzu-Gamber» is also very large – the peculiarity of this epos is being consisted from quatrains which are the lyric genre of commonturk folklore of its poetical texts spread from Romania to the land of Gagauz, from Azerbaijan to the land of Turkmen, from Turkey to Eastern Azerbaijan. Poems-quatrains, manis and so on are generally common or alike in different variants of the epos «Arzu-Gamber». The subject of the epos «Arzu-Gamber» is a love story.